Language Variation of Generation Z in TikTok Live Buying and Selling Interactions: A Linguistic Economics Perspective - Asriani Abbas; Abbas Abbas; Sony Tian Dhora; Sitti Rabiah (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2026)
The development of digital communication technology has transformed language practices within social media–based commercial interactions. In digital commerce, language functions not only as a means of communication but also as symbolic capital that shapes social identity, strengthens interpersonal engagement, and supports transaction effectiveness. This study aims to identify the language variations employed by Generation Z during buying and selling interactions on TikTok Live and examine their communicative and economic functions from a linguistic economics perspective. A descriptive qualitative approach was used through non-participant observation of interactions between Generation Z sellers and buyers on TikTok Live. Data were collected using screen recordings, screenshots, and field notes during a one-month observation period and analyzed through qualitative coding. The analysis identified four forms of language variation: abbreviations, code-mixing, puns, and emojis. These linguistic resources function as communicative and economic strategies that improve communication efficiency, strengthen audience engagement, and enhance persuasive interaction in digital commerce. Abbreviations facilitate rapid communication, code-mixing projects a modern and global identity, puns foster interpersonal closeness, and emojis reinforce emotional expression and persuasive intent. These findings contribute to digital sociolinguistics by explaining language adaptation in live commerce, extend linguistic anthropology by illustrating the relationship between Generation Z language practices and digital culture, and enrich the economics of language by demonstrating how linguistic choices create communicative value that supports commercial interaction. This study is limited to one month of TikTok Live observations; therefore, future research should examine longer observation periods and compare language practices across different live commerce platforms.